The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Le loup et le musulman : le racisme est-il une menace écologique? - Hage, Ghassan (Wildproject, 2017)
L'anthropologue explique que le loup et le musulman sont deux grandes figures fantasmatiques apparaissant comme une menace pour la civilisation, régie par la domestication et la volonté de gouverner. En effet, selon lui, le crime écologique et le crime racial relèvent d'une illusion domesticatrice, dans la mesure où ni le climat ni les âmes ne peuvent être gouvernés.
Keywords: 2000 à aujourd'hui; 2010-2019; anthropologie; approches et analyses; cours; discipline; discours dominant; environnement; fem3400; pol5480; premier cycle; périodes historiques; racisme; sciences humaines; systèmes d'oppressions; thématiques; violences

Ethnographier la violence dans la prostitution : effets du contexte, effets du terrain et force des émotions - Mayer, Sibylla (Parcours antrhopologiques, 2016)
Dans cet article, je prends pour objet une enquête passée, menée sur la prostitution de rue. Partant du vécu d’une émotion forte en aval de la recherche, après la sortie du terrain et après la discussion des résultats, je m’interroge sur la place des émotions dans l’enquête, en particulier en lien avec l’ethnographie de la violence dans la prostitution. En revenant sur le meurtre d’une personne connue sur le terrain et sur ce que cet événement a suscité en termes de retour sur ma démarche, je montre notamment que les émotions agissent en modifiant notre vécu, y compris en aval du terrain, nous permettant de revenir sur notre positionnement face à l’objet de recherche.
Keywords: 2000 à aujourd'hui; 2010-2019; anthropologie; approches et analyses; discipline; ethnographie; europe; luxembourg; point de vue situé; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail; travail du sexe; violences; émotions